The Discourse of Islamophobia in Indonesian Popular Movie “Mencari Hilal” (2015) - Rahayu, Mundi (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2021)
Most of the study of Islamophobia, the hatred and fear of Muslims, take the locus in Western countries in which Muslims are a minority group. The present study aims at answering the gap of study. This study specifically discusses the Islamophobia represented in popular culture, in a movie entitled “Mencari Hilal.” Discussion in this paper covers two questions. First, how is the discourse of Islamophobia represented in the film? Second, what is the ideology represented in the film? The present article is based on two arguments. First, Islamophobia does not only happen in Western countries. Instead, the phobia also happens within Muslim communities. Second, the film is a popular cultural text that reflects people's anxiety and desire, as well as expresses important problems that people encounter in history. This study applies Fairclough’s CDA with three levels of analyses, micro, meso, and macro. The discourse of Islamophobia in this movie is presented in more subtle ways, but the potential conflict is obviously represented. The ideology of pluralism is implied in this film to give the space for the audience to think and rethink their religious assumptionKeywords: Ancient tombs; preservation; cultural heritage.